2011
DOI: 10.1016/j.febslet.2011.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Role of a propeller loop in the quaternary structure and enzymatic activity of prolyl dipeptidases DPP-IV and DPP9

Abstract: a b s t r a c tThe dipeptidyl peptidase (DPP) family members, including DPP-IV, DPP8, DPP9 and others, cleave the peptide bond after the penultimate proline residue and are drug target rich. The dimerization of DPP-IV is required for its activity. A propeller loop located at the dimer interface is highly conserved within the family. Here we carried out site-directed mutagenesis on the loop of DPPIV and identified several residues important for dimer formation and enzymatic activity. Interestingly, the correspo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
14
0
1
Order By: Relevance
“…However, they found that the arm of DPP9 was not essential for dimerization, because a DPP9 construct lacking a large part of the predicted arm (amino acids corresponding to Ile 288 -Tyr 305 ) is correctly folded and forms dimers. Interestingly, the deletion mutant was less active compared with the wild-type protein (50). The reason for the reduced activity is currently not understood.…”
Section: Sumo1 Binds To An Arm-like Structure In Dpp9-mentioning
confidence: 96%
See 2 more Smart Citations
“…However, they found that the arm of DPP9 was not essential for dimerization, because a DPP9 construct lacking a large part of the predicted arm (amino acids corresponding to Ile 288 -Tyr 305 ) is correctly folded and forms dimers. Interestingly, the deletion mutant was less active compared with the wild-type protein (50). The reason for the reduced activity is currently not understood.…”
Section: Sumo1 Binds To An Arm-like Structure In Dpp9-mentioning
confidence: 96%
“…Recently, Tang et al (50) showed that DPPIV mutants, deleted of the arm motif fail to dimerize and are less active. However, they found that the arm of DPP9 was not essential for dimerization, because a DPP9 construct lacking a large part of the predicted arm (amino acids corresponding to Ile 288 -Tyr 305 ) is correctly folded and forms dimers.…”
Section: Sumo1 Binds To An Arm-like Structure In Dpp9-mentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the crystal structures of DPP8 and DPP9 have not yet been solved, protein homology modeling has shown that DPP8 and DPP9 likely share a similar tertiary structure with DPPIV and FAP (32,33). DPP8 (34) and DPP9 (35) are dimeric, with each monomer likely consisting of an a/b-hydrolase domain and an 8 blade b-propeller domain and the active site of the peptidase locates at the interface of these 2 domains (Fig. 2) (3,23).…”
Section: Protein Modelmentioning
confidence: 99%
“…Second, single-point mutations in the C-terminal loop, such as F822A, V833A, Y844A, and H859A in DPP8 (34), or F842A in DPP9 (40) inactivate these proteases without disrupting dimerization. Similarly, a deletion mutation (residues 317-334) or a single-point mutation (Y334A) in a propeller loop in DPP9 can cause decreased activity without affecting dimerization (35). Thus, the C-terminal loop and the propeller loop are essential for DPP8 and DPP9 enzyme activity but not for dimerization.…”
Section: Protein Modelmentioning
confidence: 99%